Creative Writing and Digital Production: Constraining and Expanding Nigeria’s Literary Production in the 21st Century (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study aims at examining the continuity and disruption of criticism, creative writing, and digital production in Nigeria’s literary Production in the 21st Century. Drawing insight from theory of remediation, data were purposively extracted from 30 social media handles such as: Facebook, Whatsapp, Instagram, Twitter, Tik Tok, blogs. In each of mentioned social media, 5 creative works were extracted and subjected to literary analysis. Some data were gotten from interviews which were conducted on final years students of the department of English and Literary studies. Between 2017 and 2022 the sample size was 100 students and 50 for each year. In 2017, 75-80% of the students seemed to be comfortable with writing poems and short stories and publishing on Facebook. While in 2022 80-90% students published their creative compositions across multiple social media platforms and providing hyperlinks to their various texts while also using emojis as symbolic language in their creative compositions and other forms of multimodality. Using the said institution as a hypothesis, most of the students seem to be voluntarily interested in literary forms on cyberspace against the print literature. The study advocates for the need to break the barriers to the study of digital literature and the need for new criticisms in the university.